The Concept of Pancasila Student Profile Towards Indonesia's Vision 2045 - Dessy Farantika; Arif Muzayin Shofwan; Heni Krisnawati; Marwan Hayeemaming (International Journal on Education Issues, 2025)
Purpose - The vision of Indonesia 2045 aims to transform the nation into a sovereign, advanced, and prosperous country. A critical pillar in achieving this goal is the development of human capital that embodies national identity while maintaining global competitiveness. This study aims to analyze the conceptual framework of the Pancasila Student Profile, exploring how its six fundamental dimensions serve as a strategic response to the evolving challenges of the 21st century and as a realization of Indonesia's national educational vision. Design/Methodology/Approach - This research utilizes a qualitative library research method. Data collection was conducted through a study of literature, reports, and books, specifically focusing on primary documents from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). The data analysis employed a descriptive-philosophical approach using deduction, induction, and comparison to synthesize the key elements of the student profile framework. Findings - The study identifies that the Pancasila Student Profile is operationalized through six essential dimensions: (1) faith, piety to God Almighty, and noble character, which encompasses morality toward nature and the state; (2) global diversity, focusing on intercultural communication and social justice; (3) mutual cooperation, involving collaboration and sharing; (4) independence, which emphasizes self-regulation and situational awareness; (5) critical reasoning, requiring the objective processing of information and metacognition; and (6) creativity, defined by original ideas and flexible problem-solving. These dimensions represent a shift from purely cognitive assessment to a holistic focus on character and global citizenship competencies. Originality/Value - The originality of this study lies in its specific alignment of the Pancasila Student Profile with the long-term trajectory of the "Indonesia 2045 Vision." While existing research focuses on localized character building, this paper provides a comprehensive theoretical roadmap that links the philosophical values of Pancasila with the practical requirements of sustainable global development. It offers significant value for educators and policymakers seeking to synchronize character-based curricula with national strategic planning.